Modulating Systemic Immune-Inflammatory Indices via Double Filtration Plasmapheresis: Implications for Aging and Low-Grade Inflammation - Castillo-Aleman, Yandy Marx; Villegas-Valverde, Carlos Agustin; Ventura-Carmenate, Yendry; Al-Karam, Maysoon; Al Dhuhaibat, Ashwag Shamkhi; Lumame, Shinnette; Rose-Roque, Jay Mary; Castelo, Charisma; Benedetti, Stefano; Al-Kaabi, Fatema Mohammed; Rivero-Jimenez, Rene Antonio; Bencomo-Hernandez, Antonio Alfonso; Bornstein, Stefan R. (Hormone and Metabolic Research, 2025)
Systemic immune-inflammatory indices derived from routine complete blood counts are useful markers of systemic inflammation across various conditions. Currently, double filtration plasmapheresis is used to lower lipid levels and remove pro-inflammatory mediators; however, its effects on systemic immune-inflammatory indices are underreported. A retrospective analysis of patients undergoing two double filtration plasmapheresis sessions for hypercholesterolemia or hyperlipoproteinemia(a) at a single center was conducted between April and July 2025. Complete blood count-derived immune-inflammatory indices and lipid profiles were measured immediately before and after the first and second double filtration plasmapheresis sessions, respectively. Intra-individual comparisons were performed using the Wilcoxon signed-rank test. Double filtration plasmapheresis performed with the Inuspheresis System significantly reduced the neutrophil-to-lymphocyte ratio (p=0.040), platelet-to-lymphocyte ratio (p=<0.001), systemic immune-inflammatory index (p=0.008), and aggregate index of systemic inflammation (p=0.048), while significantly increasing lymphocyte-to-monocyte ratio (p=<0.001); systemic inflammation response index did not change significantly. Expected reductions were also observed in total cholesterol, LDL cholesterol, HDL cholesterol, triglycerides, and lipoprotein(a), all with p <0.001. In addition to its lipid-lowering effects, double filtration plasmapheresis modulated short-term systemic immune-inflammatory indices, indicating potential utility for these metrics as surrogate markers of acute systemic inflammation and immunomodulation. Given their availability from routine complete blood counts, monitoring these indices could aid individualized patient assessment during double filtration plasmapheresis. These results may also help refine personalized care in patients with low-grade inflammation and aging-related immune dysfunction.
Keywords: aging; hypercholesterolemia; immunomodulation; inflammation mediators; plasmapheresis; hyperlipoproteinemia